Catastrophic mortality of southern elephant seals caused by H5N1 avian influenza - Campagna, Claudio; Uhart, Marcela María; Falabella, Valeria; Campagna, Julieta; Zavattieri, Victoria; Vanstreels, Ralph E. T.; Lewis, Mirtha Noemi (Marine Mammal Science)
We report on the first outbreak of high pathogenicity H5N1 avian influenza, causing extreme mortality in the southern elephant seal, Mirounga leonina, at Península Valdés (PV) and nearby areas, in Argentina. The virus was con-firmed by the Argentine Government Animal Health Service (SENASA) on samples collected from elephant seals at PV. Findings were reported by the national authorities to the World Organisation for Animal Health and are available through the World Animal Health Information System under event ID 5189 (specifically, outbreaks OB_126883 and OB_124986). Fil: Campagna, Claudio. Wildlife Conservation Society; Estados Unidos. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Uhart, Marcela María. Universidad Nacional del Centro de la Provincia de Buenos Aires; Argentina. University of California at Davis; Estados Unidos Fil: Falabella, Valeria. Wildlife Conservation Society; Estados Unidos Fil: Campagna, Julieta. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Wildlife Conservation Society; Estados Unidos Fil: Zavattieri, Victoria. Wildlife Conservation Society; Estados Unidos Fil: Vanstreels, Ralph E. T. University Of California At Davis. School Of Veterinary Medicine; Estados Unidos Fil: Lewis, Mirtha Noemi. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina